Screening dan Strategi Pencegahan Delirium Pada Lansia Di Puskesmas Andalas Padang - Willady Rasyid; Weni Mailita (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
Gunungsari Village, Sukaratu District, is one of the areas affected by the COVID-19 pandemic, because the majority of the people there head their families work outside the area and also work as traders and farmers. During the pandemic they cannot return to work, as well as traders and farmers, they cannot market their agricultural products to the fullest. With the regulation that people have to stay at home, apart from the difficulty in earning income, it also creates a new problem, namely the increase in plastic waste, especially plastic bottles, because in general they consume instant food and drinks. Plastic waste that continues to increase can cause serious problems if not treated immediately. To reduce the abundance of plastic waste, especially plastic bottles, there must be innovations that have a utilization goal. The concept of using plastic bottle waste as aquaponic planting media in the yard is an alternative to maintain food security so that food needs are met. In this service the methods used are planning, implementing actions, reflection, and evaluation. Results What is achieved from this service activity is increasing public knowledge about managing home yards for aquaponic cultivation to fulfill nutrition and help the community's economy